Operasi Plastik dalam Islam: Tinjauan tentang Kebutuhan, Prinsip Syariah, dan Pertimbangan Etis - Naila Azzahra; Azkia Zahra Safa; Luthfina Noor Afrila (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
This research examines the practice of plastic surgery from the perspective of Islamic law, which is increasingly relevant in the modern era with increasing aesthetic demands. Plastic surgery is divided into two types: reconstructive, which is permitted for medical purposes, and aesthetic, which is generally prohibited if not supported by clear medical reasons. This study is based on the principles of maslahah and madlorot, as well as the ijtihad of the ulama, which shows that medical procedures are permissible if they bring benefits and avoid harm. This research also highlights the challenges Muslims face due to unrealistic beauty standards, especially on social media, which often conflict with religious values. The research results show the importance of religious education that emphasizes self-acceptance and building a community that supports diversity in appearance. Suggestions for ethical medical practice in plastic surgery are also proposed, so that the procedure is in line with Islamic principles. In this way, it is hoped that Muslims can navigate modern demands without sacrificing religious values.